Cohort Profile Update: The Irish Longitudinal Study on Ageing (TILDA). - Mc Garrigle, Christine; Kenny, Rose; Meaney, James; Scarlett, Siobhan; Ward, Mark (My University, 2018)
As outlined in the original cohort profile,1 The Irish Longitudinal Study on Ageing (TILDA) is a prospective cohort study designed to provide an evidence base for addressing the challenges and opportunities associated with population ageing in Ireland. The sampling and study design are described in Whelan et al.2 Briefly, the sampling frame is based on the Irish Geodirectory, a comprehensive and up-to-date listing and mapping of all residential addresses in the Republic of Ireland, compiled by An Post (the Irish Postal Service) and Ordnance Survey Ireland.3 Participants were randomly selected using the RANSAM sampling procedure, so that each residential address in Ireland had an equal probability of selection. Community-dwelling adults aged 50 years and over and their spouses (of any age) who were non-demented and able to provide informed consent were eligible to participate. There are three components to data collection: (i) a computer-assisted personal interview (CAPI) administered by trained social interviewers in the participants’ own homes; (ii) a self-completion questionnaire (SCQ) completed in the participants’ own time; and (iii) a comprehensive health assessment delivered by trained research nurses in a dedicated health centre, or a modified version delivered in the participant’s home. Baseline interviews on 8504 participants took place between October 2009 and February 2011; 85% and 72% of these participants completed the SCQ and health assessment, respectively. The first four waves of the study, scheduled to take place every 2 years, was funded by the Irish Government, The Atlantic Philanthropies and Irish Life plc. Ethical approval for each wave of data collection was obtained from the Trinity College Dublin Faculty of Health Sciences Research Ethics Committee. What is the reason for the new focus and new data collection? There are two main reasons for the cohort profile update. First, three additional waves of data collection have been completed since the profile was originally published.1 As data are analysed and collaborative opportunities became available, the research focus has been refined and consequently new questions and tests have been included. A notable change to the health assessment was the addition of the magnetic resonance imaging (MRI) brain sub-study in Wave 3, funded through the Irish Health Research Board. Ethical approval for the MRI sub-study was obtained from St James’ Hospital Research Ethics Committee. Second, a number of new features have been introduced to cater for changes in participant circumstances. From Wave 2 onwards, proxy interviews were obtained to provide a greater insight into the lives and experiences of individuals who experience severe cognitive or physical decline, and end-of-life (EOL) interviews provide insight into the final year of life, particularly around health care use. This paper provides an update on data collected in Waves 2, 3 and 4 and describes the refined research focus.
PUBLISHED
Keywords: Ageing